2017
DOI: 10.1016/j.apcatb.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic performances of ZnO nanoparticle film and vertically aligned nanorods in chamber-based microfluidic reactors: Reaction kinetics and flow effects

Abstract: The nanoparticle seed layer (a film) and vertically aligned nanorods of zinc oxide (ZnO) with different lengths were fabricated within a novel chamber-based microfluidic (microchamber) reactor with a varying height of 0.127-5mm and characterized with their microstructures, photocatalytic performances as well as qualitative reaction kinetics. The ZnO seed layer was produced by a sol-gel procedure and the nanorods were hydrothermally grown on seed layer coated glass substrates. These ZnO samples were integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 34 publications
0
28
0
Order By: Relevance
“…There are also microreactors (microfluidic reactors) which have been gaining research attention in the design of pollutant remediation systems in contrast to the conventional macroscale reactors (CoMRs) (Hamaloğlu et al 2017;Zhao et al 2017c;de Sá et al 2018;Yusuf et al 2018;Rashmi Pradhan et al 2019). Unlike the case of CoMRs which are impeded in their performance because of mass transfer limitations and poor photon management (Jayamohan et al 2016;Zhao et al 2017c), microfluidic reactors are characterized by the presence of a thin liquid layer on the surface of the catalyst which limits the loss of photons (Jayamohan et al 2016).…”
Section: Developments In the Design Of Photocatalytic Reactor Processesmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also microreactors (microfluidic reactors) which have been gaining research attention in the design of pollutant remediation systems in contrast to the conventional macroscale reactors (CoMRs) (Hamaloğlu et al 2017;Zhao et al 2017c;de Sá et al 2018;Yusuf et al 2018;Rashmi Pradhan et al 2019). Unlike the case of CoMRs which are impeded in their performance because of mass transfer limitations and poor photon management (Jayamohan et al 2016;Zhao et al 2017c), microfluidic reactors are characterized by the presence of a thin liquid layer on the surface of the catalyst which limits the loss of photons (Jayamohan et al 2016).…”
Section: Developments In the Design Of Photocatalytic Reactor Processesmentioning
confidence: 99%
“…There are also microreactors (microfluidic reactors) which have been gaining research attention in the design of pollutant remediation systems in contrast to the conventional macroscale reactors (CoMRs) (Hamaloğlu et al 2017;Zhao et al 2017c;de Sá et al 2018;Yusuf et al 2018;Rashmi Pradhan et al 2019). Unlike the case of CoMRs which are impeded in their performance because of mass transfer limitations and poor photon management (Jayamohan et al 2016;Zhao et al 2017c), microfluidic reactors are characterized by the presence of a thin liquid layer on the surface of the catalyst which limits the loss of photons (Jayamohan et al 2016). There are key advantages which are associated with microfluidic reactors, namely that they offer more interaction of species involved with the catalysts because of greater surface-to-volume ratio, they have shorter diffusion distance, better mass transport, higher photocatalytic efficiency (Meng et al 2013;Jayamohan et al 2015), low consumption of reagents, decreased generation of waste materials and reduced energy consumption.…”
Section: Developments In the Design Of Photocatalytic Reactor Processesmentioning
confidence: 99%
“…2A). 48,76 Specifically, along the flow direction, the length of nanowires decreased and the morphology changed from pyramidal tops to flat tops. 48,49 By modulating the synthesis parameters such as the seed preparation, residence time, and heating locations, ZnO nanowire arrays could be synthesized either on the entire substrate/patterned area, 53,57,78 or along the microheaters inside the microchannel (Fig.…”
Section: Continuous Laminar Flow Synthesismentioning
confidence: 99%
“…Microfluidic chips have attracted great attention for catalytic applications due to their inherently large surface-to-volume ratios, short diffusion distance, rapid mass transfer, and high integration capabilities. By easy interfacing with UV light, microchips find great application in photocatalysis for the photodegradation of methylene blue (MB), 50,60,73 phenol, 85 methyl orange, 76 and volatile organic compounds (benzene, toluene, ethylbenzene, m-p xylenes, and o-xylene). 79 ZnO nanowires have a high electron transfer rate and could be grown on a patterned area over a glass substrate 60,76 (Fig.…”
Section: Molecular Catalysismentioning
confidence: 99%
“…9 are used. Zhao et al 54 recently studied the effectiveness of a ZnO nanorod based system formed using a combination of sol gel and hydrothermal syntheses in a microfluidic chamber type reactor. The authors of this work observed a large improvement over the batch type process, ascribing this to improved mass transport when run in flow.…”
Section: Reactor Systemsmentioning
confidence: 99%